2020
DOI: 10.1007/s10984-020-09318-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving learning environments through whole-school collaborative action research

Abstract: The focus of professional learning on activities has changed to internal growth or change among teachers. Our three-year whole-school collaborative action research was based on student feedback from a learning environment survey at a secondary school. Quantitative data were obtained by administering a survey in 2012, 2013 and 2014 to 2673 students in 171 classes to assess perceptions of the learning environment. Qualitative information, involving classroom observations and interviews with the principal and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Over time, this simple approach evolved into more-sophisticated methods for scoring questionnaires and graphically depicting feedback about students’ perceptions of actual and preferred learning environments. For example, case studies of successful environment improvement studies have been reported for teacher action research (Aldridge et al, 2012 ) and a principal-led whole-school improvement effort (Aldridge et al, 2021 ).…”
Section: Discussion Limitations and Further Researchmentioning
confidence: 99%
“…Over time, this simple approach evolved into more-sophisticated methods for scoring questionnaires and graphically depicting feedback about students’ perceptions of actual and preferred learning environments. For example, case studies of successful environment improvement studies have been reported for teacher action research (Aldridge et al, 2012 ) and a principal-led whole-school improvement effort (Aldridge et al, 2021 ).…”
Section: Discussion Limitations and Further Researchmentioning
confidence: 99%
“…A caring thinking skills inventory was developed to give an idea about the summative evaluation of the program before and after the curriculum. Although the program delivery based action research requires the use of data collection tools based on qualitative data in accordance with the nature of qualitative research such as action research, case study, quantitative measurement tools can also be used to make a summative evaluation of the program (Aldridge, Rijken and Fraser, 2021;Ramlal and Augustin, 2020;Vire Quezada and Santillán, 2021).…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Teachers collaboration positively impact teacher practices and student learning (Weddle et al, 2020). According to the study by Aldridge et al (2020), teachers are more likely to think about their classroom actions, evaluate them, and transform their practices when the interactions between them increase. Furthermore, according to Zamir (2020), to enhance and ensure the effectiveness of the school and meet the demands of various parties, the school must have a strategy for management practices.…”
Section: Repetition Ratementioning
confidence: 99%